A review on Friction Stir Welding in Aluminium Alloys. Issue 1 (October 2020) - Stephen Leon, J; Bharathiraja, G; Jayakumar, V
Abstract: Joining of aluminium alloys is always a challenging task due to its easily oxidising property in its molten stage. Although its application is huge in the building of aerospace structure, 2XXX and 7XXX series alloys are categorised as non-weldable aluminium alloys. Recent development in the application of friction stir welding process in the joining of these non-weldable alloys simplified the fabrication processes. In this review article, significance of friction stir welding comparing with other solid state metal joining process is addressed. Recent developments and application of this relatively new metal joining process in various industries are also discussed. Particular emphasis has been given to the mechanism responsible for the formation of this solid state joining technique. Apart from this, major process parameters that influence the formation of weld and weld defects caused by the improper selection of process parameters are also explained in detail.